1999
DOI: 10.1093/fampra/16.5.468
|View full text |Cite
|
Sign up to set email alerts
|

GPs' views on their role in cancer genetics services and current practice

Abstract: GPs readily identify a role for themselves in cancer genetics services, but admit to a lack of confidence in this area, calling for clear referral guidelines and specialist community support. Current inappropriate referral to specialist services results from a lack of confidence in estimating cancer risk, highlighting the need for the development of clear referral criteria. Given the rapidly increasing demand for cancer genetics services and the vital role of primary care, it is important to identify a model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
112
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 14 publications
6
112
1
Order By: Relevance
“…Patients with chronic diseases preferred their GP as source of genetic information, and to a lesser degree information sheets, medical specialists, and the media [28,29]. As a family doctor, the GP is in a good position to provide genetic information [37], which is something GPs themselves agree with [38,39]. Unfortunately, GPs feel unconfident about their ability to do so, as their genetic expertise falls short [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with chronic diseases preferred their GP as source of genetic information, and to a lesser degree information sheets, medical specialists, and the media [28,29]. As a family doctor, the GP is in a good position to provide genetic information [37], which is something GPs themselves agree with [38,39]. Unfortunately, GPs feel unconfident about their ability to do so, as their genetic expertise falls short [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…As a family doctor, the GP is in a good position to provide genetic information [37], which is something GPs themselves agree with [38,39]. Unfortunately, GPs feel unconfident about their ability to do so, as their genetic expertise falls short [38][39][40]. The Netherlands Ministry of Health, Welfare and Sport acknowledges that health care providers lack the knowledge and skills to adequately provide genetic information.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative models for how nurse counsellors might provide a risk assessment service include the concept of working in liaison or outreach settings (Emery et al, 1999;Fry et al, 1999). Two randomised controlled trials have reported on different models of service delivery for genetic counselling for risk of breast cancer (Brain et al, 2000;Fry et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In reality, however, general practitioners (GPs) find this 'gatekeeper' role difficult, both in the UK (Fry et al, 1999;Bankhead et al, 2001;Rose et al, 2001;Walter et al, 2001;Elwyn et al, 2002;Campbell et al, 2003) and elsewhere (Escher and Sappino, 2000). The proportion of referrals to breast cancer family clinics that fall below the required risk threshold has been reported as almost 25% in one large UK-wide survey (Wonderling et al, 2001).…”
mentioning
confidence: 99%